Map of Mass Movement in a Region of the State of Sao Paulo, Brazil - Palmeira, Otavio Furiatto [UNESP]; Palcheco Peixoto, Anna Silvia [UNESP]; Kaiser, Ilza Machado [UNESP]; LopezAcosta, N. P.; MartinezHernandez, E.; EspinosaSantiago, A. L.; MendozaPromotor, J. A.; Lopez, A. O. (Ios Press, 2019)
In the past fifteen years, there has been a significant increase of the number of natural disasters on a world scale. Specifically in Brazil, this increase is mainly related to the growth of urbanization leading to unsuitable buildings and deforestation on hillsides causing social and economic problems. Hence, studies are needed to better understand the triggering factors and the communities' response capacity. The purpose of this paper is to come up with a hazard map of mass movement in the region of the Paraiba Valley and North Coast of the state of Sao Paulo, Brazil. The data of mass movement were managed according to Natural Disasters Database of Center of Meteorology, Sao Paulo State University (UNESP) considering the period between 1996 to 2016. All the occurrences were georeferenced allowing detailed study of the physical characteristics such as geomorphology, geology, geotechnics and land use. In order to do so, the data were analyzed statistically according to the occurrence numbers. The trigger rains analyses considered daily rains, 3 days and 7 days before the occurrence. The quantification of the hazard used a matrix that combined socionatural criteria with rainfall thresholds. Three maps were done based on daily rains, 3 days and 7 days and it was concluded that the 3 days rain were the most relevant.
Keywords: Mass movement map; natural hazard; triggering agent